Culture and economy after the cultural turn - Ray, Larry J.; Sayer, R. Andrew; Sage eBooks (London : SAGE, 1999)
Traditionally, social science has treated culture as a peripheral issue. However, over the last twenty years, culture has moved to the core of the debate. This volume examines the impact of this transformation on the major social sciences.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Culture; Social sciences; Electronic books